Analisis Etika Profesi BK terhadap Pelaksanaan Layanan Konseling Berbasis Online - Pardamean Harahap, Akhir; Lutfi Nasution, Marzuki; Hanum Safni, Laila; Izzatunnisa, Yasmin; Penemuan Nasution, Arie; Syapitri (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The development of the internet for information and communication has given rise to a new design approach known as Online-based Counseling. This style, influenced by technological advances, has become easier to achieve due to existing trends. Advances in communication technology have opened up new possibilities for counselors to be creative, especially in the application of e-counseling as a way for counselors to provide alternative methods in dealing with matters related to counseling. Nevertheless, the aim of this article is to examine the influence of Bk ethics on the provision of online counseling services. For this situation, a qualitative approach is used. Utilize scientific literature from national and international academic journals, including resources such as Google Scholar.